CONVENTIONAL BANK CUSTOMER MIGRATION POST THE IMPLEMENTATION OF SHARIA FINANCIAL INSTITUTIONS QANUN NO. 11 YEAR 2018 IN ACEH - Simahatie, Mai; Asmuni, Asmuni; Rokan, Mustapa Khamal; Umikaromah, Umikaromah (Universitas Dharma Wacana, 2023)
The results of the study show that Perceived Behavioral Control formed by Control beliefs has no effect on Customer behavior with Intentions as an intervening variable on Banking Customers in Aceh Province After the Implementation of Qanun LKS NO. 11 of 2018, this again proves that banking customers in Aceh do not look at whether they are capable of carrying out a behavior or not, they also do not look at whether the experience given to them is good or not so far it has not influenced their behavior in choosing banking.